2010
DOI: 10.1108/03090561011032685
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new model of “customer compliance” service provision

Abstract: Purpose:In the last 10 years, businesses taking advantage of market deregulation, call-centre, Intranet and Internet technology have broken traditional marketing norms and path dependent customer management practices. These businesses offer substantially lower prices and good customer service. In spite of anecdotal evidence of the high level of service complaints in the press, these businesses are expanding rapidly by growing the market and by taking share from traditional suppliers. Service failure recovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 88 publications
2
24
0
2
Order By: Relevance
“…To this end the results of our study identify several organisational practices reduce the influence of customer non-compliance on service quality, which in this research was found negative in agreement with previous studies (e.g. Kasabov & Warlow, 2010;Lin & Hsieh, 2011). Specifically, the results of the analysis indicate that three organizational variables have a negative moderating effect on the aforementioned relationship: customer orientation, SB effectiveness and employee empowerment.…”
Section: Conclusion -Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…To this end the results of our study identify several organisational practices reduce the influence of customer non-compliance on service quality, which in this research was found negative in agreement with previous studies (e.g. Kasabov & Warlow, 2010;Lin & Hsieh, 2011). Specifically, the results of the analysis indicate that three organizational variables have a negative moderating effect on the aforementioned relationship: customer orientation, SB effectiveness and employee empowerment.…”
Section: Conclusion -Discussionsupporting
confidence: 81%
“…This helps the company to effectively implement the service plan and meet the predefined quality standards (Kasabov & Warlow, 2010). Also, it helps the company standardise the service process and offer a more reliable service to customers.…”
Section: The Negative Impact Of Customer Non-compliance On Perceived mentioning
confidence: 99%
See 2 more Smart Citations
“…As a conclusion: complaint management represents an important element within a defensive marketing strategy and it supports a company's ability to react to market needs and changes fast and effectively (Kasabov and Warlow 2010). Successful complaint management supports a company in protecting its market share by keeping its customer base satisfied, even if dissatisfaction could occur.…”
Section: Advantages Of Complaining Customersmentioning
confidence: 93%